Biosensor-based approach identifies four distinct calmodulin-binding domains in the G protein-coupled estrogen receptor 1. - Quang-Kim Tran; Mark Vermeer (PLoS ONE)
The G protein-coupled estrogen receptor 1 (GPER) has been demonstrated to participate in many cellular functions, but its regulatory inputs are not clearly understood. Here we describe a new approach that identifies GPER as a calmodulin-binding protein, locates interaction sites, and characterizes their binding properties. GPER coimmunoprecipitates with calmodulin in primary vascular smooth muscle cells under resting conditions, which is enhanced upon acute treatment with either specific ligands or a Ca(2+)-elevating agent. To confirm direct interaction and locate the calmodulin-binding domain(s), we designed a series of FRET biosensors that consist of enhanced cyan and yellow fluorescent proteins flanking each of GPER's submembrane domains (SMDs). Responses of these biosensors showed that all four submembrane domains directly bind calmodulin. Modifications of biosensor linker identified domains that display the strongest calmodulin-binding affinities and largest biosensor dynamics, including a.a. 83-93, 150-175, 242-259, 330-351, corresponding respectively to SMDs 1, 2, 3, and the juxta-membranous section of SMD4. These biosensors bind calmodulin in a strictly Ca(2+)-dependent fashion and with disparate affinities in the order SMD2>SMD4>SMD3>SMD1, apparent K d values being 0.44 ± 0.03, 1.40 ± 0.16, 8.01 ± 0.29, and 136.62 ± 6.56 µM, respectively. Interestingly, simultaneous determinations of biosensor responses and suitable Ca(2+) indicators identified separate Ca(2+) sensitivities for their interactions with calmodulin. SMD1-CaM complexes display a biphasic Ca(2+) response, representing two distinct species (SMD1 sp1 and SMD1 sp2) with drastically different Ca(2+) sensitivities. The Ca(2+) sensitivities of CaM-SMDs interactions follow the order SMD1sp1>SMD4>SMD2>SMD1sp2>SMD3, EC50(Ca(2+)) values being 0.13 ± 0.02, 0.75 ± 0.05, 2.38 ± 0.13, 3.71 ± 0.13, and 5.15 ± 0.25 µM, respectively. These data indicate that calmodulin may regulate GPER-dependent signaling at the receptor level through multiple interaction sites. FRET biosensors represent a simple method to identify unknown calmodulin-binding domains in G protein-coupled receptors and to quantitatively assess binding properties.